LINQ, the future of data access in C♯ 3.0 - Hummel, Joe (O'Reilly short cuts., 2006)
Language Integrated Query (LINQ) is Microsoft's new technology for powerful, general purpose data access. This technology provides a fully-integrated query language, available in both C♯ 3.0 and VB 9.0, for high-level data access against objects, relational databases, and XML documents. In this Short Cut you'll learn about LINQ and the proposed C♯ 3.0 extensions that support it. You'll also see how you can use LINQ and C♯ to accomplish a variety of tasks, from querying objects to accessing relational data and XML.